Brassinosteroids Improve Quality of Summer Tea (Camellia sinensis L.) by Balancing Biosynthesis of Polyphenols and Amino Acids - Li, Xin; Ahammed, Golam J.; Li, Zhi-Xin; Zhang, Lan; Wei, Ji-Peng; Shen, Chen; Yan, Peng; Zhang, Li-Ping; Han, Wen-Yan (Frontiers in Plant Science, 2016)
Summer grown green tea is less popular due to bitterness and high astringency that are attributed to high levels of tea polyphenol (TP) and low levels of amino acids (AA) in tea leaves (Camellia sinensis L.). Brassinosteroids (BRs), a group of steroidal plant hormones can regulate primary and secondary metabolism in a range of plant species under both normal and stress conditions. However, specific effects of BRs on the photosynthesis of tea plants and the quality of summer green tea are largely unknown. Here we show that 24-epibrassinolide (EBR), a bioactive BR, promoted photosynthesis in tea plants in a concentration-dependent manner. Stimulation in photosynthesis by EBR resulted in an increased summer tea yield. Although all tested concentrations (0.01, 0.05, 0.1, 0.5 and 1.0 ppm) increased concentrations of TP and AA, a moderate concentration of EBR (0.5 ppm) caused the highest decrease in TP to AA ratio, an important feature of quality tea. Time-course analysis using 0.5 ppm EBR as foliar spray revealed that TP or AA concentration increased as early as 3 h after EBR application, reaching the highest peak at 24 h and that remained more or less stable. Importantly, such changes in TP and AA concentration by EBR resulted in a remarkably decreased but stable TP to AA ratio at 24 h and onward. Furthermore, concentrations of catechins and theanine increased, while that of caffeine remained unaltered following treatment with EBR. EBR improved activity of phenylalanine ammonia-lyase (PAL) and glutamine: 2-oxoglutarate (GOGAT) enzymes involved in catechins and theanine biosynthesis, respectively. Transcript analysis revealed that transcript levels of CsPAL and CsGS peaked as early as 6 h, while that of CsGOGAT peaked at 12 h following application of EBR, implying that EBR increased the concentration of TP and AA by inducing their biosynthesis. These results suggest a positive role of BR in enhancing green tea quality, which might have potential implication in improving quality of summer tea.